IMPLEMENTING HOLISTIC DEVELOPMENT APPROACHES THROUGH PLAY-BASED LEARNING FOR INFANTS AND TODDLERS IN TASKA - NUR JAZMINA BATRISYIA FADZIL; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study examines the implementation of holistic development approaches through play-based learning for infants and toddlers in TASKA. The research emphasizes the significance of play as a foundation for nurturing children’s physical, cognitive, social, emotional, and language growth. The primary goal is to investigate how holistic components can be successfully incorporated into regular educational activities to promote development that is both balanced and meaningful. An early childhood educator was interviewed using a qualitative approach to learn more about their practices, comprehension, and difficulties when implementing play-based learning. The results show that play-based learning improves positive educator-child interactions while fostering creativity, problem-solving, communication, and emotional well-being. Overall, the study concludes that implementing holistic, play-centered methods contributes significantly to the comprehensive development of young children and improves the quality of early childhood education in TASKAsettings.